Leader-member exchange theory in higher and distance education - Robert Leo Power (Athabasca University Press, 2013)
Unlike many other prominent leadership theories, leader-member exchange (LMX) theory does not focus on the specific characteristics of an effective organizational leader. Rather, LMX focuses on the nature and quality of the relationships between a leader and his or her individual subordinates. The ideal is for a leader to develop as many high-quality relationships as possible. This will lead to increases in subordinates’ sense of job satisfaction and organizational citizenship, as well as to increased productivity and attainment of organizational goals. LMX has been criticized for its potential to alienate some subordinates, failing to account for the effects of group dynamics and social identity, and failing to provide specific advice on how leaders can develop high-quality relationships. However, LMX has been heralded as an important leadership theory in higher and distance educational contexts because of its emphasis on promoting autonomy and citizenship, as well as its ability to complement and mediate transformational leadership styles. Recent authors have attempted to provide specific advice for leaders who want to learn how to build and capitalize on the high-quality relationships described by LMX theory.